2022
DOI: 10.3390/polym14040746
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Electrospun Polycaprolactone Nanofibers Reinforced by Halloysite Nanotubes for Tissue Engineering

Abstract: Due to its slow degradation rate, polycaprolactone (PCL) is frequently used in biomedical applications. This study deals with the development of antibacterial nanofibers based on PCL and halloysite nanotubes (HNTs). Thanks to a combination with HNTs, the prepared nanofibers can be used as low-cost nanocontainers for the encapsulation of a wide variety of substances, including drugs, enzymes, and DNA. In our work, HNTs were used as a nanocarrier for erythromycin (ERY) as a model antibacterial active compound wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Accordingly, it seems that the PCL + HNTs composite sample containing 5%HNTs to be as a more proper substrate for cell adhesion compared to the other nanocomposites and neat PCL scaffold samples. Similar results were observed with previous studies, in which PCL scaffolds with 6%HNTs showed proper nanofiber structure 22 …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, it seems that the PCL + HNTs composite sample containing 5%HNTs to be as a more proper substrate for cell adhesion compared to the other nanocomposites and neat PCL scaffold samples. Similar results were observed with previous studies, in which PCL scaffolds with 6%HNTs showed proper nanofiber structure 22 …”
Section: Resultssupporting
confidence: 92%
“…Similar results were observed with previous studies, in which PCL scaffolds with 6%HNTs showed proper nanofiber structure. 22…”
Section: Morphological Investigation Of Electrospun Fiberous Matsmentioning
confidence: 99%
“…[25][26][27] Several studies have been reported on the electrospinning of PCL. [28][29][30][31] However, encapsulating watersoluble agents in PCL scaffolds is challenging because its hydrophobic nature limits drug-polymer interactions (e.g., hydrogen bonding). Moreover, another problem is the solubility of water-soluble agents in the organic solvents that t PCL.…”
Section: Introductionmentioning
confidence: 99%
“…25–27 Several studies have been reported on the electrospinning of PCL. 28–31 However, encapsulating water-soluble agents in PCL scaffolds is challenging because its hydrophobic nature limits drug–polymer interactions ( e.g. , hydrogen bonding).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the impressive improvement in flexibility of PCL was investigated in [ 13 ] that can be used for many applications in tissue engineering. In [ 14 ], PCL nanofibers were refined by halloysite nanotubes for tissue engineering. A novel electrospun nanofiber membrane was fabricated in [ 15 ] that consists of PCL, chitosan oligosaccharides, and Qe/Rutin as the potential bioactive dressing for wound healing that regardless other combinations was limited to poor water solubility [ 16 ].…”
Section: Introductionmentioning
confidence: 99%